Exploring the Thickness-Dependence of the Properties of Layered Gallium Sulfide - Gutiérrez, Yael; Giangregorio, Maria M.; Dicorato, Stefano; Palumbo, Fabio; Losurdo, Maria (Frontiers in Chemistry, 2021)
Group-III layered monochalcogenide gallium-sulfide, GaS, is one of the latest additions to the two-dimensional (2D) materials family, and of particular interest for visible-UV optoelectronic applications due to its wide bandgap energy in the range 2.35 - 3.05 eV going from bulk to monolayer. Interestingly, when going to the few-layers regime, changes in the electronic structure occur, resulting in a change in the properties of the material. Therefore, a systematic study on the thickness dependence of the different properties of GaS is needed. Here, we analyze mechanically exfoliated GaS layers transferred to glass substrates. Specifically, we report the dependence of the Raman spectra, photoluminescence, optical transmittance, resistivity and work function on the thickness of GaS. Those findings can be used as guidance in designing devices based on GaS.